SIMULATION AND DESIGN OF AREA-EFFICIENT BUILT-IN SELF-TEST TECHNIQUE WITH MAXIMIZING TEST COVERAGE (International Journal of Food and Nutritional Sciences, 2021)
With the semiconductor industry pushing the boundaries of integrated circuit (IC) design and manufacturing, there is a greater demand than ever for reliable and efficient testing techniques. This abstract uses a novel "Area-Efficient Built-In Self-Test" (AEBIST) approach to explore the intricate link between test coverage and chip area consumption. This work's primary objective is to explore the most effective ways to maximize silicon real estate utilization while resolving the challenges associated with creating AEBIST approaches that provide complete test coverage. Traditional external testing methods sometimes cannot keep up with the increasing complexity and heterogeneity of today's integrated circuits (ICs). In response, AEBIST—which embeds independent testing circuits right into the chip—appears to be a workable substitute. The core concepts of AEBIST design are examined in this article, emphasizing the technology's inherent ability to maximize test coverage through strategic placement of test circuits that minimizes impact on chip area. Test pattern generators, signature analyzers, and efficient fault detection algorithms are used to ensure that AEBIST helps identify faults without consuming too much chip space.The importance of adapting to AEBIST methods is also emphasized in the abstract. It discusses how these techniques can be modified to suit a range of applications, ensuring that the particular testing needs of different integrated circuits are met while maintaining area efficiency. AEBIST methodologies provide an adaptable structure for achieving superior test coverage by accommodating varying design considerations and testing goals.